O potrzebie wiedzy humanistycznej. Ku wychowaniu człowieka zintegrowanego. Próba wskazania tropów - Joachimowska , Magdalena (Studia Edukacyjne, 2020)
The content of the article was created during the search for justification for, stated in the subject literature, the need for the existence of an integrated (trans-disciplinary) science about humans; this need to gather existing knowledge which allows for a comprehensive and holistic understanding about an individual, their essence (both humans and their humanity) and their activity encouraging the education of a person ready to take responsibility for the quality of their life resulting from reflection and understanding. Bringing up self-aware and thinking people, who realize themselves in their personal, professional and social life, who are responsible for themselves, others, and the world around them. The aim of the conducted analysis was also to search for a common language (common categories and meanings) of researchers from various scientific fields (philosophy, anthropology, sociology, pedagogy, physics, law, history, mathematics and others) and various cultures concerned about their existence, and thus about the existence of an individual and their humanity.